Optimalization of human capital and social capital for economic empowerment, case study in Topa Bajo Traditional Tribe - La Ode Zahaba; Ujianto Ujianto; Ferdinandus Sampe; Sunu Priyawan (Institute of Computer Science (IOCS), 2023)
This study aims to investigate to optimize the synergy of social capital and human capital to influence economic empowerment in a traditional marine tribe, the Bajo Topa tribal community. The relevance of social capital and human capital that contribute to economic empowerment in the Bajo ethnic community was investigated. The social structure both in the micro and macro spheres and how relationships are established between them based on values, norms, sanctions, beliefs, and social networks as reliable forces in solving problems or social needs. The research was conducted using qualitative methods using interviews and observations. The results reveal that the Bajo Topa tribal community is homogeneous both ethnic and occupation which consists of a large family community (dansihitang). Social capital bonding performance is high both in the trust and networking aspects. The relevance of human capital and social capital are most likely to be anchored to the social structure of the Bajo Topa tribal community. Intermodal synergy can be applied to increase the Bajo Topa society economic empowerment in the form of complete synergy, including; social capital, human capital, physical capital and economic capital